THE EFFECTS OF CRITICAL FACTORS ON ORGANIZATIONAL CHANGE OF THAI GARMENT FIRMS - Panthong, Orramon (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2017)
The objectives of this study are to investigate the level of organizational change in Thai garment firms together with examining the critical factors affecting organizational change. How Thai garment firms take change actions in strategies and plans, work processes, organizational structure, and organizational culture are also explored for better understanding of change implementation. The mixed method research design is employed by in-depth interviews together with the surveys. The samples are 344 garment firms in Thailand. The results reveal that the overall organizational change of Thai garment firms is moderate level. Organizational culture appears to be more remarkable altered than other components, following by organizational strategies and plans, work processes, and organizational structure, respectively. The stepwise multiple regression indicates that, among five critical factors which positively affect organizational change implementation of Thai garment firms, employee participation has the greatest contribution following by international trade policies, sense of urgency for change, economic situations, and technology advancement. Several change actions are implemented, for example, the revision of prior paternalistic management culture to the professional management style, the shift on manufacturing and investment plans by relocating production bases to CLMV countries and the modification of marketing strategies with product differentiation as well as the alteration of targeted market to niche market instead of mass market. The findings of this study benefits not only individual garment firms but also Thailand garment industry to design appropriate strategies for responding uncertainty and managing change in an effective way.